CHARACTERISTICS OF FERMENTED ARJUNO ROBUSTA COFFEE BY COMMERCIAL BAKER’S YEAST - Maligan, Jaya Mahar; Hernanto, Danang Pratomo; Wulan, Siti Narsito (Jurnal Pangan dan Agroindustri, 2024)
This research focused on the fermentation of coffee beans using commercial yeast containing S. cerevisiae with variations in fermentation duration (5, 10, and 15 hours) and yeast concentration (0%, 1%, 2%, and 3%). The research aimed to understand how fermentation duration and yeast concentration affect the physical, aroma, and sensory characteristics of Robusta Arjuno coffee. The research employed a Randomized Block Factorial Design (RBFD) and ANOVA. The analysis results indicated that the coffee bean samples met SNI standards, including ash content, ash alkalinity, and coffee extract.  The fermentation duration, yeast concentration, and interaction had no significant impact on attributes such as aroma, taste, aftertaste, acidity, body, balance, sweetness, uniformity, and overall quality. However, fermentation duration did affect the "clean cup" factor. Robusta Arjuno coffee with  3% yeast addition and a fermentation duration of 10 hours received the highest score (85.52), indicating the best quality in the cupping test.